Using accounting systems based on computer processing of accounting data - Kogut, O. U. (Journal of Economic Research & Business Administration, 2015)
The article considers the advantages of computer accounting systems: computer processing involves the use of the same commands when performing identical operations of accounting, which virtually eliminates the occurrence of random errors usually inherent in manual processing of accounting data.